Seed-transmitted Epichloë sp. endophyte alleviates the negative effects of head smut of grasses (Ustilago bullata) on Bromus auleticus - Iannone, Leopoldo Javier (2017)
Some grasses are co-infected by ‘castrator’ fungal pathogens, such as Ustilago bullata, and beneficial seed-transmitted Epichloë endophytes that compete for plant photosynthates and flowers. Epichloë-infected (E+) and Epichloë-free (E−) seeds of Bromus auleticus were inoculated (S+) or not (S−) with teliospores of U. bullata and an experiment under field conditions was performed to evaluate the effect of these fungal infections on different host plant traits. Head smut disease incidence was almost 0% in E+ treatment whereas in endophyte-free plants the disease incidence reached 33%, a result in concordance with the lower number of seeds produced by E−S+ plants. Neither the smut nor the endophyte affected seedling emergence or growth. Plant survival was significantly decreased by the smut in E− plants and was associated with a higher biomass production in E+ treatments. Our results provide new insights about the ecology of Epichloë endophytes and their protective and growth-promoting role in the interaction of its host with U. bullata.